The obstetrical management of HIV-positive pregnancy - Mihai George Loghin; Petre Gabriel Gorescki; Romina Marina Sima; Liana Pleș; Daniela Gabriela Balan; Ioana Paunica; Oana Denisa Bălălău (Journal of Mind and Medical Sciences)
The human immunodeficiency virus (HIV) infection is a real public health problem in both developing and developed countries. HIV infection has not been treated efficiently for a long time, with HIV-positive women at increased risk of transmitting the infection to their newborns. Without the appropriate treatment, the evolution of the infection is relatively fast. Due to the antiretroviral treatment, the progression of the disease is blocked during the period of asymptomatic infection, and the risk of neonatal transmission is very low. HIV-positive patients undergoing antiretroviral therapy develop undetectable viremia and, in such situations, patients no longer have a risk of transmitting the infection. The antiretroviral medication is a combination of several classes of drugs (protease inhibitors, nucleoside and non-nucleoside reverse transcriptase inhibitors, integrase inhibitors and CCR5 inhibitors) whose aim is to stop the viral replication at different stages. The infection is most often transmitted in the perinatal period, so it is very important that we know the maternal viremia and choose the type of birth with the lowest risk of transmitting the infection to the fetus. For this reason, any HIV-positive patient with detectable viremia at childbirth should receive treatment during labor and delivery, with a nucleoside or non-nucleoside reverse transcriptase inhibitor that crosses the fetal-placental barrier.